Socio Economic Assessment and Environmental Practices of Mangrove Area Settlers in Davao Gulf - Tan, Esther Consuelo (JPAIR Multidisciplinary Research, 2008)
This research proceeded from the premise that population impacts on the environment and vice versa. The characteristics and behavior of the population living proximate to the mangrove areas, migration patterns and intentions as well as their economic activities in many ways affect the quality and state of the mangrove system. This study is a descriptive research. It utilized a standardized questionnaire for socio-economic survey. It used focus group discussion to establish a time line of historical events in the mangrove areas. The results of the study found out that that the respondents are highly dependent on fishing as their livelihood. The respondents claimed that they have to augment their income through other means because of the degradation of the mangrove areas. The degradation of the mangrove areas is attributed to in-migration of the people coming from other regions and the upland and the conversion of the area because of economic development. The proper authority should enforce existing laws and policies and sustain programs on mangrove protection and conservation. Approaches to mangrove conservation should include information, education and communication ( IEC) program.
Keywords: Mangrove; Environmental Practices